Hedgehog-regulated ubiquitination controls smoothened trafficking and cell surface expression in Drosophila. - Shuang Li; Yongbin Chen; Qing Shi; Tao Yue; Bing Wang; Jin Jiang (PLoS Biology, 2012)
Hedgehog transduces signal by promoting cell surface expression of the seven-transmembrane protein Smoothened (Smo) in Drosophila, but the underlying mechanism remains unknown. Here we demonstrate that Smo is downregulated by ubiquitin-mediated endocytosis and degradation, and that Hh increases Smo cell surface expression by inhibiting its ubiquitination. We find that Smo is ubiquitinated at multiple Lysine residues including those in its autoinhibitory domain (SAID), leading to endocytosis and degradation of Smo by both lysosome- and proteasome-dependent mechanisms. Hh inhibits Smo ubiquitination via PKA/CK1-mediated phosphorylation of SAID, leading to Smo cell surface accumulation. Inactivation of the ubiquitin activating enzyme Uba1 or perturbation of multiple components of the endocytic machinery leads to Smo accumulation and Hh pathway activation. In addition, we find that the non-visual β-arrestin Kurtz (Krz) interacts with Smo and acts in parallel with ubiquitination to downregulate Smo. Finally, we show that Smo ubiquitination is counteracted by the deubiquitinating enzyme UBPY/USP8. Gain and loss of UBPY lead to reciprocal changes in Smo cell surface expression. Taken together, our results suggest that ubiquitination plays a key role in the downregulation of Smo to keep Hh pathway activity off in the absence of the ligand, and that Hh-induced phosphorylation promotes Smo cell surface accumulation by inhibiting its ubiquitination, which contributes to Hh pathway activation.